2011
DOI: 10.1088/1468-6996/12/5/054210
|View full text |Cite
|
Sign up to set email alerts
|

Development of compact CW-IR laser deposition system for high-throughput growth of organic single crystals

Abstract: We developed a compact continuous-wave infrared (CW-IR) laser deposition system for the high-throughput growth of organic single crystals. In this system, two CW-IR lasers are used for the sample heating and thermal evaporation of materials. The CW-IR laser heating is simple and allows good control of the deposition rate and growth temperature, in response to the on/off laser switching. Six samples can be loaded simultaneously in a chamber, which allows one-by-one sequential deposition for high-throughput expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Furthermore, an infrared (IR) laser deposition technique for organic material deposition might be useful for this purpose; this process is similar to PLD, but an IR laser is used instead of a UV laser. 53,54…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an infrared (IR) laser deposition technique for organic material deposition might be useful for this purpose; this process is similar to PLD, but an IR laser is used instead of a UV laser. 53,54…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an infrared (IR) laser deposition technique for organic material deposition might be useful for this purpose; this process is similar to PLD, but an IR laser is used instead of a UV laser. 53,54 Furthermore, readers may have received a rather negative impression due to the minimal discussion about direct structure-property relationshipseven the semi-quantitative onesfrom the studies on compositionally graded crystal materials that have been so far published. For this reason, we would like to emphasize that this is arguably one of the biggest challenges that must be overcome to further develop compositionally graded crystal materials with new functionalities.…”
Section: Discussionmentioning
confidence: 99%
“…C 60 was deposited by a CW-IR laser deposition technique at temperatures of 50 to 120 uC and at supply rates of 2.7 to 10 nm min 21 . 8,17 The supply rate was monitored by a quartz crystal microbalance (QCM) sensor to precisely control the total amount of deposited C 60 for all samples. C 60 (sublimed, 99.9%) was purchased from Sigma-Aldrich and used as received in all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…14 We also demonstrated that some ILs can be used in the vacuum deposition of atomically flat epitaxial KBr (111) microcrystals, 15 pentacene 16 and C 60 single microcrystals. 17 In all these cases, the crystal quality was dramatically improved, particularly with regards to their crystal size. The most characteristic of the ILmediated vacuum deposition is that a quasi-thermodynamic equilibrium condition can be achieved at temperatures high above room temperature via a repeated cycle of dissolution and recrystallization during the crystal growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation